A social semiotic analysis of instructional images across academic disciplines. (February 2016) - Wilson, Amy Alexandra; Landon-Hays, Melanie
Framed in theories of social semiotics, this descriptive multiple case study examined the images used by six middle-school teachers during one school year as they each taught two different subject areas: earth science, language arts, mathematics, and/or social studies. Using Kress and Van Leeuwen's visual grammar to analyze these images, this study identified discipline-specific patterns in how 1, 132 images realized assumptions in regards to the ideational and interpersonal metafunctions of communication. A content analysis suggested discipline-specific differences in the presumed social distance between the content of the images and the students, as well as discipline-specific differences in assumptions about the subjectivity of knowledge. Instructional implications are suggested, such as encouraging students to critique the assumptions in images and selecting a wider array of image types in each discipline.